Implementasi Program Sistem Informasi Desa Siap (Opensid) di Desa Siwalan Kecamatan Panceng Kabupaten Gresik - Muhammad Annas Subakti; Tjitjik Rahaju (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Policy implementation is an effort to realize objectives through operational programs. The Village Government of Siwalan implemented the Village Information System Program (OpenSID) as part of the digital transformation initiated by the Gresik Regency Government under Regent Regulation No. 38 of 2023. This study aims to describe the implementation of OpenSID in Siwalan Village using a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using George C. Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate several challenges in implementation, particularly in communication, limited human and financial resources, lack of incentives, and the absence of standard operating procedures (SOPs). The study recommends improving communication strategies, developing SOPs, strengthening human resource capacity, providing incentives, and upgrading to the premium version of OpenSID.